Massive Gene Loss and Function Shuffling in Appendicularians Stretch the Boundaries of Chordate Wnt Family Evolution - Martí-Solans, Josep; Godoy-Marín, Hector; Diaz-Gracia, Miriam; Onuma, Takeshi A.; Nishida, Hiroki; Albalat, Ricard; Cañestro, Cristian (Frontiers in Cell and Developmental Biology, 2021)
Gene loss is a pervasive source of genetic variation that influences species evolvability, biodiversity and the innovation of evolutionary adaptations. To better understand the evolutionary patterns and impact of gene loss, here we investigate as a case study the evolution of the wingless (Wnt) family in the appendicularian tunicate Oikopleura dioica, an emergent EvoDevo model characterized by its proneness to lose genes among chordates. Genome survey and phylogenetic analyses reveal that only four of the thirteen Wnt subfamilies have survived in O. dioica—Wnt5, Wnt10, Wnt11, and Wnt16,—representing the minimal Wnt repertoire described in chordates. While the loss of Wnt4 and Wnt8 likely occurred in the last common ancestor of tunicates, representing therefore a synapomorphy of this subphylum, the rest of losses occurred during the evolution of appendicularians. This work provides the first complete Wnt developmental expression atlas in a tunicate and the first insights into the evolution of Wnt developmental functions in appendicularians. Our work highlights three main evolutionary patterns of gene loss: (1) conservation of ancestral Wnt expression domains not affected by gene losses; (2) function shuffling among Wnt paralogs accompanied by gene losses; and (3) extinction of Wnt expression in certain embryonic directly correlated with gene losses. Overall our work reveals that in contrast to “conservative” pattern of evolution of cephalochordates and vertebrates, O. dioica shows an even more radical “liberal” evolutionary pattern than that described ascidian tunicates, stretching the boundaries of the malleability of Wnt family evolution in chordates.